An Investigation of Environmental Factors that Influence Student's Decision to Study Information Technology: A Qualitative Approach - Xolisa Philip Piyose; Murimo Bethel Mutanga; Sithembile Lydia Ndovela (Journal of Information Systems and Informatics)
Selecting a career path is crucial for students' future success and job market readiness. This study underscores the need to align education with career goals for an easier transition from school to work. It highlights the importance of environmental factors, academic performance, and personal factors in influencing students' career decisions. While many studies focus on social and academic impacts, few explore the environmental aspects affecting the career choices of Information Technology (IT) students. This research aims to fill this gap by investigating these environmental influences using a qualitative approach, concentrating on comprehensive examinations through questionnaires and focus group discussions. The specific scientific research objectives are to identify and analyse the key environmental factors that influence IT students' career choices; and to understand how these factors interact with personal and academic considerations to shape career decisions. By exploring the effects of technological advancements, media trends, societal expectations, and access to IT resources, the study seeks to uncover the core substance of environmental influences on career orientation within the IT field. It involves a diverse student group from various educational and socio-economic backgrounds. The findings reveal a strong influence of technological advancements and media trends on students' perceptions of IT careers, showing a keen responsiveness to new technologies and media representations. In contrast, societal and cultural factors like family expectations and peer pressure have a lesser effect. The study emphasises the importance of resources like IT infrastructure and early technology exposure in career choices. It suggests that educational institutions and policymakers should consider these elements to develop effective strategies. Addressing societal norms, ensuring equal resource access, and improving information availability are key. Such measures can help prepare a skilled generation, contributing to the technological field and societal advancement.